Approaching the Zero‐Power Operating Limit in a Self‐Coordinated Organic Protonic Synapse - Shuzhi Liu; Zhilong He; Bin Zhang; Xiaolong Zhong; Bingjie Guo; Weilin Chen; Hongxiao Duan; Yi Tong; Haidong He; Yu Chen; Gang Liu (Advanced Science, 2023)
Abstract High‐performance artificial synapse with nonvolatile memory and low power consumption is a perfect candidate for brainoid intelligence. Unfortunately, due to the energy barrier paradox between ultra‐low power and nonvolatile modulation of device conductances, it is still a challenge at the moment to construct such ideal synapses. Herein, a proton‐reservoir type 4,4′,4″,4'''‐(Porphine‐5,10,15,20‐tetrayl) tetrakis (benzenesulfonic acid) (TPPS) molecule and fabricated organic protonic memristors with device width of 10 µm to 100 nm is synthesized. The occurrence of sequential proton migration and interfacial self‐coordinated doping will introduce new energy levels into the molecular bandgap, resulting in effective and nonvolatile modulation of device conductance over 64 continuous states with retention exceeding 30 min. The power consumptions of modulating and reading the device conductance approach the zero‐power operating limits, which range from 16.25 pW to 2.06 nW and 6.5 fW to 0.83 pW, respectively. Finally, a robust artificial synapse is successfully demonstrated, showing spiking‐rate‐dependent plasticity (SRDP) and spiking‐timing‐dependent plasticity (STDP) characteristics with ultra‐low power of 0.66 to 0.82 pW, as well as 100 long‐term depression (LTD)/potentiation (LTP) cycles with 0.14%/0.30% weight variations.